Coming Out ? Revealing One?s Own Existence - Kopciewicz, Lucyna; Welenc, Marcin (INSTED: Interdisciplinary Studies in Education & Society, 2012)
In the article the writers present possible ways of theoretising the process of coming out placing it in the course of changes which were faced by the phenomenon of homosexuality (medicalisation, decriminalisation, strategy of building the minority visibility, HIV/AIDS crisis and queer policy). Coming out is presented as a series of speech acts during which the homosexuality is revealed, which is referred to by the reference books as a risky, but payable turning point in an individual biography. In this meaning of coming out the role of interpellations understood as so call for disclosure is examined. Another meaning of coming out is connected with building a strategy of the visibility of a minority social movement (defining sexual identity). The last of these meanings refers to new ?frames of visibility?, where the homosexual community became known through AIDS.